Optical properties of solids - Fox, Mark (Anthony Mark) (Oxford master series in physics, 2010)
"The innovative text gives an introductory treatment of the optical properties of solids. The fundamental principles of absorption, reflection, luminescence and light scattering are discussed for a wide range of materials, including crystalline insulators and semiconductors, glasses, metals, and molecular materials. Classical and quantum models are used as appropriate, and the phenomena are well illustrated using recent experimental data. A particular feature is the inclusion of many new topics that have come to the fore in recent years and have not previously been covered in other solid state texts at this level. Examples include semiconductor quantum wells, organic semiconductors, vibronic solid state lasers and nonlinear optics."--Pub. desc